Intraoperative Anesthetic Management in an Asymptomatic and Biochemically Silent Pheochromocytoma - N., Omar; M., Shahid; Bashir, M.; S., Imran; K., Vipin; D., Palak (International Journal of Innovative Research in Medical Science, 2021)
Pheochromocytomas are tumors that originate from the chromaffin tissue of the adrenal medulla and commonly produce catecholamines. The diagnosis is typically established by the measurement of catecholamines or their metabolites in urine or plasma and tumors are localized with the use of radiographic and scintigraphic studies. Pheochromocytomas can occur in asymptomatic patients and the preferred treatment is surgical removal of the tumor. These chromaffin tissue tumors are not uncommon in anesthetic practice and have varied manifestations. The perioperative management of these tumors has improved remarkably over the yearsin conjunction with the evolution of surgical techniques (laparotomy to laparoscopic techniques and now to robotic approaches.). Majority of the patients present with normal clinical and biochemical parameters in the preoperative period, the incidence of hypertension being only 50 %. Even though patients may be clinically asymptomatic, surveillance and proper preoperative evaluation is important, as surgery for associated tumors may precipitate a hypertensive crisis and result in severe complications. We report an intraoperative anesthetic management of 32-year-old female with a left adrenal mass (pheochromocytoma) and left ovarian cyst. Throughout her entire course of treatment she was asymptomatic with normal blood pressure readings. Her biochemical screening was unremarkable. She underwent open surgical resection of the adrenal mass with confirmation of pheochromocytoma on histology. Pheochromocytoma represents very significant challenges to the anesthesiologist’s especially when undiagnosed. This case illustrates how paucity of literature on perioperative preparation of clinically and biochemically silent Pheochromocytomas led to serious intraoperative complications even in an asymptomatic, biochemically negative patient.